Pengaruh Efikasi Diri, Self Esteem dan Kendali Diri terhadap Kinerja Pegawai pada Dinas Perhubungan Kota Lubuklinggau dengan Variabel Self Esteem sebagai Moderasi - Dewi Sindi Rama Yanti; Dheo Rimbano; Apandi Apandi; Muhammad Efenndi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of self-efficacy, self-esteem, and self-control on employee performance at the Lubuklinggau City Transportation Agency, and to test the role of self-esteem as a moderating variable. The problem of this study is based on the phenomenon of decreasing employee performance productivity caused by the inability of employees to complete tasks independently, lack of motivation, and suboptimal teamwork. This study uses a quantitative method with an associative design. The sample in this study were 56 State Civil Apparatus (ASN) employees who were selected purposively. Data collection techniques were carried out through observation, questionnaires, interviews, and documentation. Data were analyzed using regression analysis with the help of statistical software. The results of the study showed that self-efficacy, self-esteem, and self-control had a significant effect on employee performance. In addition, self-esteem was proven to be able to moderate the relationship between self-efficacy and self-control on employee performance. These findings indicate that internal psychological factors play a very important role in supporting optimal employee performance in government organizations